PROPRIETĂȚILE BIOMATERIALELOR UTILIZATE PENTRU REALIZAREA IMPLANTURILOR DENTARE- STUDIU RETROSPECTIV - Anca Mihaela Vitalariu; Diana Diaconu-Popa; Monica Tatarciuc (Romanian Dental Association for Education, 2017)
The aim of this retrospective study was to identify published studies on metallic and non-metallic dental implants, in order to make a comparative analysis of their properties. Material and method. To identify the items needed for the study, we used the PubMed database and the keywords: dental implant, titanium dental implant, zirconium dental implant, polymers dental implant. The search focused on articles published between 1995 and 2016. The inclusion criteria were as follows: (1) English language, (2) dental implants of zirconia, titanium or polymers, (3) in vitro studies, (4) in vivo studies, (5) year of publication. Results. A total of 158 articles have been identified, of which only 90 met the inclusion criteria. The studied aspects were: (1) material properties, (2) surface properties, (3) osteointegration.